2017
DOI: 10.1186/s12889-017-4210-2
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of needle and syringe Programmes in people who inject drugs – An overview of systematic reviews

Abstract: BackgroundNeedle and syringe programmes (NSP) are a critical component of harm reduction interventions among people who inject drugs (PWID). Our primary objective was to summarize the evidence on the effectiveness of NSP for PWID in reducing blood-borne infection transmission and injecting risk behaviours (IRB).MethodsWe conducted an overview of systematic reviews that included PWID (excluding prisons and consumption rooms), addressed community-based NSP, and provided estimates of the effect regarding incidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
104
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(115 citation statements)
references
References 36 publications
4
104
0
7
Order By: Relevance
“…The MeSH term "opioid-related disorders" (U.S. National Library of Medicine), includes abuse, addiction, and dependence and any kind of opioid or opiate (e.g., heroin, morphine, codeine), from which we selected the six subtopics that aligned most closely with prevention, harm reduction, and treatment efforts: diagnosis, drug therapy, prevention and control, rehabilitation, therapy, and epidemiology. These subtopics became the basis of our final query, to which we added the MeSH term "needle-exchange programs" (found under the sub-heading "Preventative Health Services" ) due to their importance as a harm reduction strategy that is not covered by any of the other search terms (Fernandes et al, 2017). This search yielded 12,166 relevant research studies.…”
Section: Sample Selection and Collectionmentioning
confidence: 99%
“…The MeSH term "opioid-related disorders" (U.S. National Library of Medicine), includes abuse, addiction, and dependence and any kind of opioid or opiate (e.g., heroin, morphine, codeine), from which we selected the six subtopics that aligned most closely with prevention, harm reduction, and treatment efforts: diagnosis, drug therapy, prevention and control, rehabilitation, therapy, and epidemiology. These subtopics became the basis of our final query, to which we added the MeSH term "needle-exchange programs" (found under the sub-heading "Preventative Health Services" ) due to their importance as a harm reduction strategy that is not covered by any of the other search terms (Fernandes et al, 2017). This search yielded 12,166 relevant research studies.…”
Section: Sample Selection and Collectionmentioning
confidence: 99%
“…In 2015, the Centers for Disease Control and Prevention (CDC) determined that 6% of HIV diagnoses in the U.S. were attributable to injection drug use (IDU) and another 3% to male-to-male sexual contact and IDU(Centers for Disease Control Prevention, 2016). The most successful, evidence-based HIV prevention effort targeting PWID is syringe service programs (SSPs), which have significantly reduced the incidence of HIV and HCV infections among PWID over the past 30 years (Fernandes et al, 2017; Gibson et al, 2001; MacDonald et al, 2003). The ongoing opioid epidemic threatens to reverse the progress that has been made on HIV prevention.…”
Section: Introductionmentioning
confidence: 99%
“…NSP is recommended to reduce the spread of HIV and hepatitis in PWID . Certain reviews have concluded that there is evidence that NSP is reducing injection risk behaviour and transmission of HIV but the data are insufficient to confirm its effectiveness in preventing the transmission of HCV . On the other hand, there are studies showing that NSP prevents HCV transmission, in particular when it is combined with OAT .…”
Section: Harm Reduction Measuresmentioning
confidence: 99%
“…16,[33][34][35] Certain reviews have concluded that there is evidence that NSP is reducing injection risk behaviour and transmission of HIV but the data are insufficient to confirm its effectiveness in preventing the transmission of HCV. [36][37][38] On the other hand, there are studies showing that NSP prevents HCV transmission, in particular when it is combined with OAT. 16,35 In a recent Cochrane report, Platt et al concluded that OAT was associated with a 50% reduction in the HCV transmission rate, while needle exchange programs (NEP) alone was less effective with a reduction of 21%.…”
Section: Harm Reduc Tion Me a Sure Smentioning
confidence: 99%